Serum Lipid Profile In Leprosy Patients In Kashmir Valley - Ahmad Qazi Masood; Hassan Iffat; Qayoom Seema; Shah Parvaiz A; Tafazul Hussain S (Wolters Kluwer Medknow Publications, 2002)
Serum lipid profile was evaluated in twenty leprosy patients (paucibacillary and multibacillary cases) and twenty age and sex matched healthy controls. The serum lipid profile of the two groups showed no statistically significant difference.